Producing and prospects for the use of bispecific antibodies for the treatment of cancer - S. E. Sedykh; G. A. Nevinsky (Успехи молекулярной онкологии)
Bispecific antibody molecules contain two different antigen-binding centers. Particular interest in bispecific antibodies is due to their therapeutic application. Two preparations of therapeutic bispecific immunoglobulins, approved for use in the US and European countries, are aimed at the treatment of cancer. Studies published in recent years are devoted to various methods of obtaining monoclonal bispecific antibodies, to study their physicochemical properties, biological activity, preclinical and clinical trials. This paper reviews different approaches  to the production of antitumor bispecific immunoglobulins, as well as the prospects for their practical application.